Perdebatan Isu Productivity Linked Wages System dalam Perundingan Kolektif Kesatuan Sekerja Perbankan Sabah - Mohd Yussof, Kee Y. Sabariah bt Kee; Ahmad, Mahadirin b. Hj (SOSIOHUMANIKA, 2009)
ABSTRACT: This paper discusses about Sabah Banking Employee Union members perception on their collective bargaining (2003-2005) on salary and payment. In their particular collective bargaining, SBEU members struggle to obtain 10 to 12 percent increament in their salary and payment. In this case, employer give them only 5% increament based on Consumer Price Indeks were lower (1.4%) during the negotition. Itâs took 21 month to negotiate and finally they come to dead lock situation. Then, SBEU invites the third party from Industrial Relation Department as a mediator in their collective bargaining process. During the last stage of negotition, the employers offered more than 5% increament in salary payment but the annual bonus would be eliminated. In this case, employers would consider the performance bonus which is evaluated from workers performance annualy. SBEU could not accept the offer as the employees would lose their annual bonus and itâs difficult to regain it back later. In positive way, the employers try to introduce the Productivity Linked Wages System in their organisation but members of SBEUÂ  disagreed with the suggestion based on saveral factors. Key words: collective bargainning, Productivity Linked Wages System, performance bonus and annualy bonus.Â Â About the Authors: Kee Y. Sabariah bt Kee Mohd Yussof, M.A. ialah Pensyarah pada Program Hubungan Industri, Sekolah Sains Sosial UMS (Universiti Malaysia Sabah). Lahir pada tahun 1976 dan berasal daripada Tawau, Sabah. Memperolehi Ijazah Sarjana Muda (2001) dan Ijazah Sarjana dalam Hubungan Industri (2006) dari UMS. Beliau berminat dalam kajian kesatuan sekerja dan perundingan kolektif. Hasil kajian beliau yang bertajuk âFaktor Pekerja Menganggotai Kesatuan Sekerja Perbankan Sabah (SBEU)â telah dibentangkan dalam Borneo Research Council 9th Biennial International Conference (29-31 July 2008). Untuk keperluan akademik, penulis dapat dihubungi dengan alamat e-mail: keesabariah@yahoo.com Mahadirin b. Hj Ahmad, M.A. ialah Pensyarah pada Program Hubungan Industri, Sekolah Sains Sosial UMS. Dilahirkan di Sandakan, Sabah pada tahun 1977. Memperolehi Ijazah Sarjana Muda dari UMS pada tahun 2001 dalam bidang Hubungan Industri dan pada tahun 2004 memperolehi Ijazah Sarjana dari UKM (Universiti Kebangsaan Malaysia) dalam bidang Antropologi dan Sosiologi. Penulis terlibat dalam kajian berkaitan masyarakat industri dan sejarah perburuhan di Malaysia. Penulis kini dalam usaha untuk menyiapkan kajian berkaitan aduan dan tuntutan pekerja di Sabah. Untuk keperluan akademik, penulis dapat dihubungi dengan alamat email: muhadir@ums.edu.myHow to cite this article? Mohd Yussof, Kee Y. Sabariah bt Kee & Mahadirin b. Hj Ahmad. (2009). âPerdebatan Isu Productivity Linked Wages System dalam Perundingan Kolektif Kesatuan Sekerja Perbankan Sabahâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.2, No.1 [Mei], pp.125-140. Bandung, Indonesia: Minda Masagi Press, UPI Bandung, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (March 6, 2009); Revised (April 9, 2009); and Published (May 20, 2009).